Naphthochromenones: Organic Bimodal Photocatalysts Engaging in Both Oxidative and Reductive Quenching Processes. Issue 3 (20th November 2019) - Mateos, Javier; Rigodanza, Francesco; Vega‐Peñaloza, Alberto; Sartorel, Andrea; Natali, Mirco; Bortolato, Tommaso; Pelosi, Giorgio; Companyó, Xavier; Bonchio, Marcella; Dell'Amico, Luca
Abstract: Twelve naphthochromenone photocatalysts (PCs) were synthesized on gram scale. They absorb across the UV/Vis range and feature an extremely wide redox window (up to 3.22 eV) that is accessible using simple visible light irradiation sources (CFL or LED). Their excited‐state redox potentials, PC*/PC .− (up to 1.65 V) and PC .+ /PC* (up to −1.77 V vs. SCE), are such that these novel PCs can engage in both oxidative and reductive quenching mechanisms with strong thermodynamic requirements. The potential of these bimodal PCs was benchmarked in synthetically relevant photocatalytic processes with extreme thermodynamic requirements. Their ability to efficiently catalyze mechanistically opposite oxidative/reductive photoreactions is a unique feature of these organic photocatalysts, thus representing a decisive advance towards generality, sustainability, and cost efficiency in photocatalysis. Abstract : Fantastic twelve naphthochromenone photocatalysts (PCs) that absorb across the UV/Vis range and feature an extremely wide redox window (up to 3.22 eV) were synthesized on gram scale. Their excited‐state redox potentials, PC*/PC .− (up to 1.65 V) and PC .+ /PC* (up to −1.77 V vs. SCE), are such that these novel PCs can engage in both oxidative and reductive quenching.